Patriotism is a High Virtue - Yusupov Arabboy Bahodirjon son; Mamadaliev Hasanbek Akmal son; Mamadaliev Xusanbek Akmal son; Yuzboev Askarbek Zafar son (Periodica Journal, 2022)
This in the article patriotism concept which degree high virtue ekani wattani jonday dear see about raw religious raw secular examples listed
Keywords: Patriotism; improved literacy; release; Judges